Sars-cov-2 host entry and replication inhibitors from Indian ginseng: an in-silico approach - Chikhale, R.V.; Gurav, S.S.; Patil, R.B.; Sinha, S.K.; Prasad, S.K.; Shakya, A.; Srivastava, S.K.; Gurav, N.S.; Prasad, R.S. (Taylor and Francis Ltd., 2020)
COVID-19 has ravaged the world and is the greatest of pandemics in modern human history, in the absence of treatment or vaccine, the mortality and morbidity rates are very high. The present investigation identifies potential leads from the plant Withania somnifera (Indian ginseng), a well-known antiviral, immunomodulatory, anti-inflammatory and a potent antioxidant plant, using molecular docking and dynamics studies. Two different protein targets of SARS-CoV-2 namely NSP15 endoribonuclease and receptor binding domain of prefusion spike protein from SARS-CoV-2 were targeted. Molecular docking studies suggested Withanoside X and Quercetin glucoside from W. somnifera have favorable interactions at the binding site of selected proteins, that is, 6W01 and 6M0J. The top-ranked phytochemicals from docking studies, subjected to 100 ns molecular dynamics (MD) suggested Withanoside X with the highest binding free energy (ΔGbind = −89.42 kcal/mol) as the most promising inhibitor. During MD studies, the molecule optimizes its conformation for better fitting with the receptor active site justifying the high binding affinity. Based on proven therapeutic, that is, immunomodulatory, antioxidant and anti-inflammatory roles and plausible potential against n-CoV-2 proteins, Indian ginseng could be one of the alternatives as an antiviral agent in the treatment of COVID 19. Communicated by Ramaswamy H. Sarma. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Withania somnifera; pandemic infection; COVID19; Indian Ayurveda; Indian Rasayana; antiviral; in-silico; molecular docking and dynamics; Ashwagandha